Degradation prediction model for friction in highways - Santos, Adriana (2014)
The purpose of this paper is to develop a multiple linear regression model that describes the pavement’s friction behaviour using a degradation evo- lution law that also considers the effects of weather, vertical alignment and traf- fic factors. This study is based on real data obtained from two different highways with an approximate total length of 43 km. These sections present different alignment features (plan/profile), different Annual Average Daily Traffic and are subject- ed to different weather conditions. Nevertheless, both comprise the same type of upper layer. The efficiency of the linear regression model in approaching and explaining da- ta was demonstrated. The most relevant factors involved in the degradation pro- cess of pavements’ friction were identified.